Stability of Cytosine-Containing Deoxyribonucleic Acid After Infection by Certain T4 rII-D Deletion Mutants - Bruner, Robert (1972)
When T-even phage infect Escherichia coli, synthesis of host deoxyribonucleic acid (DNA) rapidly ceases. If the phage carry a mutation in a gene essential for phage DNA synthesis, then the infected bacteria should make no DNA, either host DNA or phage DNA. However, we have found that infection with certain T4 gene 56 (deoxycytidine triphosphatase)-rII double mutants leads to substantial DNA synthesis. Only rII deletion mutations which extend into the middle third of the adjacent, nonessential D region lead to the anomalous DNA synthesis, when combined with a gene 56 mutation; the requirement probably is that the deletion extend into the D2a transcriptional unit identified by Sederoff et al. Genetic evidence indicates that the observed anomalous DNA synthesis is synthesis of phage DNA. We suggest that the D2a region controls, directly or indirectly, a nuclease involved in the breakdown of cytosine-containing DNA. In the absence of the D2a product, the cytosine-containing phage DNA made by the gene 56 mutant is stabilized.